Moving to another country: Understanding the characteristics of the neighbourhood environment that influence the wellbeing of older Chinese immigrants. Issue 134 (August 2022) - Gao, Siyao; Dupre, Karine; Bosman, Caryl
Abstract: Urban areas are increasingly affected by population ageing and immigration, raising new questions for urban planning and development. This study seeks to understand the relationships between transportation experiences of minority older groups and their wellbeing. This study involves 30 older Chinese immigrants who are living on the Gold Coast, Australia. Qualitative methods used to understand this relationship include in-depth interviews, travel diaries and mapping exercises. The research results confirm that older Chinese immigrants' preferred lifestyles influence their daily activities and transportation experiences. The key barriers encountered by participants include safety, accessibility of (deemed) essential facilities, quality and provision of walking paths, legibility of road networks, and the availability of public transport services to appropriate/desired destinations. ﻿This study not only enriches the knowledge of how transportation can influence the wellbeing of older Chinese immigrants. It also highlights the need to provide inclusive neighbourhood environments for minorities and vulnerable older people in cities.